A NOTE ON MAGNETIC MODELLING WITH REMANENCE - Furness P. (My University, 2001)
The general problem of magnetic modelling involves accounting for the effect of both remanent magnetization and the application of an external magnetic field. However, as far as the disturbing field of a magnetic body in a magnetic environment is concerned, there is an equivalence between the effects of these two causations that allows the remanence to be represented in terms of an equivalent primary magnetic H field. Moreover, due to the linearity of the magnetic field in terms of its causations, the general modelling problem involving an applied magnetic field in the presence of remanence can be simply and more efficiently dealt with in terms of an equivalent primary field acting in the absence of any remanent magnetization.
Keywords: MAGNETIC MODELLING; MAGNETIC REMANENCE; INTEGRAL EQUATION